Human Trafficking in Malaysia: The Right of Women and Children (2010-2019) - Ahmad, Abdullahi Ayoade; Noor, Nursairah Farhana Mohd; Ramlan, Ain Zulaikha (Advances in Social Sciences Research Journal, 2022)
Human trafficking is gaining attention internationally as a serious human rights violation. Today, almost every nation of the world is affected by human trafficking activities. Cases that are involving women and children trafficking are among the primary concern in Malaysia today. Besides, trafficking in women and children is a violation of human rights, mostly in the forms of sexual exploitation and forced labor. It threatens the security and the socio-economic condition of Malaysia. Human trafficking is commonly occurring within the perimeter of cross borders, it influences high numbers of women and children being trafficked due to poverty or internal unrest. Majority of them are originated from the neighborhood ASEAN member states and Malaysia is seen as a transit country. This paper deliberates on issue of human trafficking in Malaysia. It examines state and international policies towards combatting human trafficking issue in order to seek an adjustable solution. Likewise, it is also regarding the human rights matter due to violations faced by the vulnerable women and children. Finally, it examines the challenges that law enforcements are confronting in combatting human trafficking in Malaysia. The study adopts descriptive qualitative research method through the use of secondary resources. It was found that Malaysia has issues in standardizing clear proceeding to determine the perpetrators of Human trafficked victims. It was proposed that enforcement agents need to be diligently experienced in handling arrest of exploiters of immigrants. Furthermore, it was equally found that Malaysia lacks adequate implementation in the process of protecting the rights of the trafficked victims. The paper proposed some input on adequate strategies for handling human trafficking in Malaysia.